DEVELOPMENT OF RESOURCE-SAVING IRRIGATION REGIMES FOR SOYBEAN VARIETIES IN SALINE MEADOW-ALLUVIAL SOILS (IN THE EXAMPLE OF BUKHARA REGION) (Proceedings of International Educators Conference, 2024)
In this article, in the conditions of saline meadow alluvial soils, the soybean varieties "Uzbek-6", "Nafis" and "Tumaris" were drip-irrigated and the pre-irrigation soil moisture was 65-70-70%, 70-75-75%, and Information on the scientific results obtained in connection with the scientific research works on obtaining a high grain yield from soybean varieties when irrigated in 75-80-80% regimes and economical use of irrigation water is presented.